A Double cross-linked strategy to construct graphene aerogels with highly efficient methylene blue adsorption performance. (February 2021) - Jiang, Lei; Wen, Yanyi; Zhu, Zhongjie; Liu, Xiufeng; Shao, Wei
Abstract: A novel lysine and EDA double cross-linked graphene aerogel (LEGA) was constructed. The prepared LEGA was utilized as a methylene blue (MB) adsorbent in the wastewater treatment. It exhibits a three-dimensional interconnected porous structure benefiting dye adsorption. Its compression property is highly enhanced with the addition of lysine. Adsorption isotherm and kinetics of MB onto LEGA were discussed. Their results show that MB adsorption onto LEGA was fitted to follow Langmuir adsorption isotherm model and the pseudo-second-order kinetic model. LEGA has an excellent adsorption capacity towards MB as high as 332.23 mg/g and its MB adsorption process is proved to be an exothermic process. The mechanism for MB adsorption onto LEGA was proposed as the ion exchange, electrostatic interaction, π-π stacking interaction and hydrogen bonding. Thus, LEGA is confirmed to be a sustainable and green MB adsorbent with highly removal efficiency in the treatment of wastewater. Highlights: LEGA as a novel graphene aerogel was constructed with a double cross-linked strategy. The prepared LEGA exhibits a three-dimensional interconnected porous structure. The mechanical property is highly enhanced with the addition of lysine. The prepared LEGA has an excellent methylene blue (MB) adsorption capacity. The mechanism for MB adsorption onto LEGA is proposed.